Certain Integral Operator Related to the Hurwitz–Lerch Zeta Function. (8th April 2018) - Wang, Xiao-Yuan; Shi, Lei; Wang, Zhi-Ren
Abstract : The aim of the present paper is to investigate several third-order differential subordinations, differential superordination properties, and sandwich-type theorems of an integral operatorW s, b f ( z ) involving the Hurwitz–Lerch Zeta function. We make some applications of the operatorW s, b f ( z ) for meromorphic functions.